HUBUNGAN ANTARA KECERDASAN NATURALIS DENGAN SIKAP PEDULI LINGKUNGAN SISWA KELAS IV SEKOLAH DASAR NEGERI GUGUS HARAPAN KECAMATAN SALO KABUPATEN KAMPAR - Elvera Rosa Rosiana; Eddy Noviana; Guslinda Guslinda (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
ABSTRACTThis research was motivated by the importance of naturalist intelligence on environmental care attitude. Naturalist intelligence is one of efforts to improve environmental awareness. Naturalist intelligence is a very important intelligence to have in this era. This kind of intelligence is needed because nowadays, the world is invaded by construction, technology and economics, which are caused by humans, so it is very necessary for people who have naturalist intelligence to devote themselves voluntarily to careand protect the earth. This study aims to determine the effect of naturalist intelligence with an environmental care attitude towards the fourth grade students of Gugus Harapan Public Elementary School in Salo District, Kampar Regency. This is a correlation research with quantitative methods. In order to obtain the data of naturalist intelligence and environmental care, this study used instrument in the form of a questionnaire. The results of the study showed that there was a relationship between naturalist intelligence and the environmental care attitude of the students of GugusHarapanelementary school in Salo District, Kampar regency. It can be seen that the value of r is 0.512 with the level of moderate relationship and naturalist intelligence influences the attitude of caring for the environment by 26.3%.